Penerapan etika batuk dalam mencegah ISPA pada masyarakat di Kelurahan Sukamaju, Palembang, Sumatera Selatan - Andriani, Linda; Fathurrachman, Alif; Indira, Dwi; Pasaribu, Rouly; Sudarto, Sudarto; Rasyid, Ahmad; Ahmad, Zen (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Upper respiratory tract infection (URTI) is a disease that is easily transmitted through the air and can be inhaled into the airway. Individuals with weakened immune systems are more susceptible to severe or recurrent URTI. Increased incidence and severity of URTI in patients can significantly affect their productivity, while in children, it can hinder their growth and development. Cough ethics are generally well practiced by health workers in professional settings. However, among the public, cough etiquette is often ignored, so airborne diseases such as URTI can easily spread. Therefore, it is necessary to conduct counseling on proper cough etiquette practices to prevent the spread of URTIs, especially in Sukamaju subdistrict, Palembang. In this counseling activity, which was attended by around 200 participants, it was revealed that previously, 90% of them did not have an understanding of proper cough etiquette. After the counseling and simulation of cough etiquette, 100% of the participants have understood and applied cough etiquette correctly. Through this community service, it is hoped that the community will continue to apply proper cough etiquette, so as to form a sustainable positive habit in preventing disease transmission, as well as improving the health and welfare of the local community.